Normative Analysis of Customary Offenses in the Criminal Code and Their Implications in West Sulawesi - Muhammad Al Habsy Ahmad (Jurnal Ilmiah Multidisiplin Amsir, 2026)
This study aims to conduct a normative legal analysis of the regulation of customary offenses (delik adat) within the Indonesian Criminal Code (KUHP) and to examine its implications for the settlement of customary law cases in Sulawesi Barat. This research employs a normative legal method by analyzing primary legal materials, including statutory regulations, particularly the KUHP, and secondary legal materials such as legal doctrines, scholarly articles, and relevant literature. The data were collected through a library research approach and analyzed qualitatively using statutory and conceptual approaches. The findings reveal that the regulation of customary offenses in the KUHP reflects the recognition of living law within society. However, its application presents several challenges, including issues of legal certainty, limitations in interpretation, and the need for harmonization between customary law and national law. Furthermore, the incorporation of customary offenses provides an opportunity for more contextual and culturally responsive dispute resolution mechanisms. Nevertheless, clearer regulatory frameworks and technical guidelines are required to prevent ambiguity in legal enforcement. This study concludes that the normative regulation of customary offenses in the KUHP has the potential to strengthen a more just and culturally grounded national legal system, particularly in resolving customary law cases in Sulawesi Barat. Therefore, it is essential to ensure normative synchronization and enhance the capacity of law enforcement authorities in understanding and implementing these provisions effectively.